Konseling Individu dengan Teknik Modeling untuk Meningkatkan Kekuatan Karakter Kesederhanaan - Cucu Arumsari (Universitas Kanjuruhan Malang, 2018)
Individual counseling with modeling techniques has been proven effective in increasing the strength of the character of temprence. Clients were very active in participating in each counseling session. Researchers can observe clients clearly on each counseling process. This study used qualitative method with types of grounded research and descriptive tchnique so that the analysis is very clear and detailed. The three counselees clients who conducted individual counseling can be analyzed experiencing an increasement in the power of temprence character. Research was conducted on three counselees, the results of the study proved effective to develop the strength of the character of temperance, it can be seen that there is evidence first counselee are able to be better at people who hurt them, able to make friends with everyone, be able to do tasks more timely and can control emotions more. second counselee also get better by being able to appreciate their friends as well as third counselee who can control emotions more when find unpleasant situations.